Modality and Code Glosses to Transition from Academic Written to Oral Discourses - Nausa, Ricardo (Íkala, Revista de Lenguaje y Cultura, 2019)
This article presents the results of a pilot study carried out in an English for Academic Purposes (EAP) class for PhD programs at a private university in Bogotá. The study sought to identify the mechanisms to change the content of academic essays to present them in oral presentations (OPs) to a multidisciplinary audience, and how such mechanisms mark differences of performance in the OPs. To identify the mechanisms of transition from written to oral mode, a discourse analysis comparison of eight parallel pairs of texts was performed. Changes to the expression of modality and the inclusion of code glosses were the mechanisms used to make the transition. These mechanisms helped students express contents in engaging and easy-to-process ways. The analysis of mechanisms includes the linguistic resources to modify sentences, their pragmatic appropriateness, and their grammatical correctness. This paper ends outlining some implications and limitations, and perspectives for future research.